6-PACK programme to decrease fall injuries in acute hospitals: Cluster randomised controlled trial - Barker, A.; Morello, R.; Wolfe, R.; Brand, C.; Haines, T.; Hill, Keith; Brauer, S.; Botti, M.; Cumming, R.; Livingston, P.; Sherrington, C.; Zavarsek, S.; et al. (2016)
Objective: To evaluate the effect of the 6-PACK programme on falls and fall injuries in acute wards. Design: Cluster randomised controlled trial. Setting: Six Australian hospitals. Participants: All patients admitted to 24 acute wards during the trial period. Interventions: Participating wards were randomly assigned to receive either the nurse led 6-PACK programme or usual care over 12 months. The 6-PACK programme included a fall risk tool and individualised use of one or more of six interventions: “falls alert” sign, supervision of patients in the bathroom, ensuring patients’ walking aids are within reach, a toileting regimen, use of a low-low bed, and use of a bed/chair alarm. Main outcome measures: The co-primary outcomes were falls and fall injuries per 1000 occupied bed days. Results: During the trial, 46 245 admissions to 16 medical and eight surgical wards occurred. As many people were admitted more than once, this represented 31 411 individual patients. Patients’ characteristics and length of stay were similar for intervention and control wards. Use of 6-PACK programme components was higher on intervention wards than on control wards (incidence rate ratio 3.05, 95% confidence interval 2.14 to 4.34; P<0.001). In all, 1831 falls and 613 fall injuries occurred, and the rates of falls (incidence rate ratio 1.04, 0.78 to 1.37; P=0.796) and fall injuries (0.96, 0.72 to 1.27; P=0.766) were similar in intervention and control wards. Conclusions: Positive changes in falls prevention practice occurred following the introduction of the 6-PACK programme. However, no difference was seen in falls or fall injuries between groups. High quality evidence showing the effectiveness of falls prevention interventions in acute wards remains absent. Novel solutions to the problem of in-hospital falls are urgently needed.